Optimalisasi penggunaan firewall dalam sistem operasi windows 11 - Syamsul Bahri (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
Windows 11 is a widely used operating system, making it a frequent target for various cyber threats such as malware, spyware, ransomware, Trojans, data theft, and system damage. This situation highlights the importance of implementing preventive measures to enhance system security. One of the security features available in Windows 11 is the firewall; however, users often fail to fully utilize it due to limited knowledge and understanding regarding its configuration and security functions. This study aims to analyze the optimization of firewall usage in Windows 11 as a preventive measure to improve system security and protection against various cyber threats. The research employs a qualitative descriptive method, utilizing a literature review and system observation. Data were gathered through observations of Windows 11 security configurations; reviews of books, journals, proceedings, and technical documentation; and the collection of system configuration guides and screenshots. Data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that the Windows 11 firewall plays a crucial role in monitoring, controlling, and filtering data traffic entering and leaving the system. Firewall optimization can be implemented across domain, private, and public networks, tailored to their specific characteristics and risk levels. In conclusion, optimizing the built-in Windows 11 firewall serves as a preventive measure that helps enhance system security while reducing the risk of cyberattacks and data loss.